(untitled) (Archive of Conferences, 2022)
Interactive methods will increase the effectiveness of learning. One of the most important requirements for Russian language lessons is teaching students independent thinking, as well as the ability to think. The basis of the use of gaming technologies is an activity that activates and accelerates students.